PERHITUNGAN EFEKTIVITAS DAN KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BANJARNEGARA TAHUN 2015 – 2019 - Silvia Melinda; Adilistiono Adilistiono (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
Regional Tax is one of the components of the Regional Original Income. One type of Local Taxes namely Restaurant Tax. The aim of this research is to determine the effectiveness and contribution of Restaurant Tax to the Regional Original Income Banjarnegara District in 2015 – 2019. Data collection is done through interview method, documentaries method and literature review method . The method of data calculation used is with the effectiveness analysis, tax contribution analysis of Restaurant to Regional Original Income as well as regression analysis and correlation to know whether the relationship between these variables is a coincidence or indeed a strong relationship. The results of this study indicate that the level of effectiveness of the Restaurant Tax on Regional Revenue District Banjarnegara Year 2015 – 2019 as a whole is very effective. But, the contribution of Restaurant Tax to Regional Original Income is still very less because from 2015 – 2019 only at 0 – 10% and the relationship between Restaurant Tax with Regional Original Income Banjarnegara Regency in positive, it means that the increase of Restaurant Tax acceptance will influence rhe increase of received Regional Original Income.